Gains from Trade and the Sovereign Bond Market - Ayumu Ken Kikkawa; Akira Sasahara (ZBW – Leibniz Information Centre for Economics, 2018)
Increasing international flows of goods, services, and financial assets have been shown to increase a country's welfare through various channels. This paper studies the interaction between a country's welfare gains from international trade and its sovereign's access to bond markets. We do so by incorporating a sovereign bond market into a simple Armington (1969) trade model. While standard trade models suggest surprisingly small gains from trade, our model implies that introducing channels through a sovereign bond market greatly magnifies the gains from trade.
Keywords: F14; F60; 330; Gains from trade; Sovereign debt; Sovereign default; Trade openness